Pengaruh Jumlah Penduduk dan Tingkat Pengangguran Terbuka terhadap Indeks Pembangunan Manusia di Provinsi Riau - Nadia Anjarsari; M. Afdal Samsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of population size and open unemployment rate on the Human Development Index (HDI) in Riau Province. The research method used is a descriptive quantitative approach with multiple linear regression analysis. The data used is secondary data based on districts/cities in Riau Province obtained from the Central Statistics Agency (BPS). The analysis results indicate that population size has a positive and significant effect on the HDI, while the open unemployment rate has a negative and significant effect. The F-test also shows that both variables simultaneously have a significant effect on the HDI. The R-squared value of 56.08% indicates that the model adequately explains the variation in the HDI. These findings suggest that improving population quality and reducing unemployment rates are key factors in enhancing human development quality in Riau Province.